Strengthening Elementary Students’ Nationalism and Patriotism through Pancasila Character Education Based on Visual Media - Fitri, Fitri (International Journal of Business, Law, and Education, 2025)
This study investigates the role of visual media–based Pancasila character education in strengthening nationalism, patriotism, and human rights awareness among elementary school students in the Society 5.0 era. Employing a qualitative case study design, the research was conducted at SDN Jurumudi 4, Tangerang City, involving Grade IV and V teachers, students, and the school principal as participants. Data were collected through classroom observations, in-depth interviews, and documentation of learning activities using images of national symbols and Pancasila values. Data analysis followed the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing with triangulation to ensure credibility. The findings reveal that visual media significantly enhance students’ understanding of abstract Pancasila values, increase learning engagement, and foster affective attachment to national identity. Image-based instruction not only supports cognitive comprehension but also cultivates empathy, discipline, and moral reflection related to human rights principles. Students demonstrated greater pride in national symbols, improved participation, and positive behavioral changes after the implementation of visual-based learning. The study concludes that integrating visual media into Pancasila character education is a strategic approach to nurturing nationalism and patriotism in elementary education. It provides a contextual learning model that bridges technological advancement with Indonesia’s foundational civic values in response to the challenges of the Society 5.0 era.